2002
DOI: 10.1016/s0042-6989(01)00278-4
|View full text |Cite
|
Sign up to set email alerts
|

Better perception of global motion after monocular than after binocular deprivation

Abstract: We used random-dot kinematograms to compare the effects of early monocular versus early binocular deprivation on the development of the perception of the direction of global motion. Patients had been visually deprived by a cataract in one or both eyes from birth or later after a history of normal visual experience. The discrimination of direction of global motion was significantly impaired after early visual deprivation. Surprisingly, impairments were significantly worse after early binocular deprivation than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 38 publications
8
135
2
Order By: Relevance
“…The existence of a restricted time window for blindness to lead to functionally specific cross-modal plasticity in right dorsal regions is consistent with previous evidence of early structural (Gogtay et al, 2004;Bourne and Rosa, 2006;Flom et al, 2009) and functional (Ellemberg et al, 2002;Fine et al, 2003;Gregory, 2003;Maurer et al, 2005) maturation of these regions. Our results also support the recent findings of Bedny et al (2010) who, focusing on hMT + /V5, reported that this region reacts more strongly to an auditory condition with higher motion content (approaching footsteps) than to a condition with lower motion content (tones increasing in intensity), in early-onset blind individuals but not in a group of five late-onset blind individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The existence of a restricted time window for blindness to lead to functionally specific cross-modal plasticity in right dorsal regions is consistent with previous evidence of early structural (Gogtay et al, 2004;Bourne and Rosa, 2006;Flom et al, 2009) and functional (Ellemberg et al, 2002;Fine et al, 2003;Gregory, 2003;Maurer et al, 2005) maturation of these regions. Our results also support the recent findings of Bedny et al (2010) who, focusing on hMT + /V5, reported that this region reacts more strongly to an auditory condition with higher motion content (approaching footsteps) than to a condition with lower motion content (tones increasing in intensity), in early-onset blind individuals but not in a group of five late-onset blind individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Visually normal adults can detect the direction of global motion accurately even when it is carried by less than 10% of the moving dots. Previously we have shown that sensitivity to global motion, as measured by our version of the task, is adult-like by 6 years of age and is impaired after early visual deprivation (Ellemberg, Lewis, Maurer, Brar, & Brent, 2002).…”
Section: Global Motionmentioning
confidence: 70%
“…The stimuli and procedure were identical to that of Ellemberg et al (2002) except that thresholds were tested with the method-of-constant stimuli rather than with a staircase procedure. BrieXy, participants viewed randomdot-kinematograms (RDKs): patterns of dots moving randomly except for a proportion that moved coherently either up or down.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…[7][8][9] Importantly, this dissociation has received substantial support from recent research showing that atypical development differentially affects global and configural skills, with the former being spared and the latter being deficient. 6,[8][9][10][11] Interestingly, a comparable dissociation has also been found in children born with congenital cataracts, 12,13 who show increased difficulties in tasks involving configural processing, such as motion 14 conditions, yet they are both characterized by exposure to the visual world at a different time from expected under normal development -early deprivation and early stimulation respectively -which could, in turn, result in atypical development of visual function. Following the line of recent studies on the development of human visuoperception, the investigation of a possible dissociation between global and configural abilities in preterm children appears of special interest.…”
mentioning
confidence: 81%